2023
DOI: 10.1002/jbt.23564
|View full text |Cite
|
Sign up to set email alerts
|

β‐lapachone protects against doxorubicin‐induced hepatotoxicity through modulation of NAD+/SIRT‐1/FXR/p‐AMPK/NF‐kB and Nrf2 signaling axis

Ashkan Kalantary‐Charvadeh,
Saeed Nazari Soltan Ahmad,
Somayeh Aslani
et al.

Abstract: Doxorubicin (DOX) is a widely used antineoplastic drug, but its clinical use is limited by significant toxicities, such as hepatotoxicity. In this study, we evaluated the effects of β‐lapachone (β‐LAP), a natural quinone‐containing compound, in a mouse model of DOX‐induced hepatotoxicity. β‐LAP was orally administered at 1.25, 2.5, and 5 mg/kg for 4 days, and a single dose of DOX (20 mg/kg) was injected intraperitoneally on the second day. Histopathological changes, liver function markers, antioxidant and infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The mechanism of doxorubicin-induced hepatotoxicity is complex, with several systems at work. Recent studies have revealed that oxidative stress play an impartment role in Dox-induced hepatotoxicity [ 2 ]. Post-transcriptional RNA modification has been linked to the regulation of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of doxorubicin-induced hepatotoxicity is complex, with several systems at work. Recent studies have revealed that oxidative stress play an impartment role in Dox-induced hepatotoxicity [ 2 ]. Post-transcriptional RNA modification has been linked to the regulation of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%